Live television : time, space and the broadcast event - Marriott, Stephanie (Media, culture, and society series., 2007)
In this accessible book, Stephanie Marriott engages in a close and detailed analysis of the nature of live television. She examines the transformations in our experience of time and space which are brought about by the capacity of broadcasting, to bring us the world in the moment in which it is unfolding.